2011
DOI: 10.1103/physrevb.84.174123
|View full text |Cite
|
Sign up to set email alerts
|

Structure and properties of the low-density phase ι-Al2O3from first principles

Abstract: Of the various phases of transition alumina, iota-alumina (ι-Al 2 O 3 ) is the least well known. It is considered to be the end member of the mullite series in the limit of zero Si content. The structural details of ι-Al 2 O 3 are not available and its physical properties are totally unknown.Based on an appropriately modified structure of a high alumina content mullite phase close to the 9-1 mullite, we have successfully constructed a structural model for ι-Al 2 O 3 . The simulated x-ray diffraction (XRD) patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…In the Reuss approximation, a uniform stress distribution is assumed, giving the lower limit through the elastic compliance tensor S ij . The average of these two limits, known as the Hill approximation, provides a realistic representation of polycrystalline bulk properties of many ceramic and metallic crystals, including those containing complex defect structures . To obtain the elastic constants of the 20 MAX phases, their crystal structures were first fully relaxed using the Vienna ab initio simulation package .…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…In the Reuss approximation, a uniform stress distribution is assumed, giving the lower limit through the elastic compliance tensor S ij . The average of these two limits, known as the Hill approximation, provides a realistic representation of polycrystalline bulk properties of many ceramic and metallic crystals, including those containing complex defect structures . To obtain the elastic constants of the 20 MAX phases, their crystal structures were first fully relaxed using the Vienna ab initio simulation package .…”
Section: Methods Of Calculationmentioning
confidence: 99%
“…Several computational studies on aluminum oxide polymorphs have been reported in recent years, which mainly apply standard DFT methods. [22][23][24][25][26][27][28][29][30] In this paper, we apply a recently developed technique based on the so-called quasi-harmonic approximation (QHA): a simple and effective method that is able to address the aforementioned issue in the case of corundum. 31,32 The thermal expansion coefficient, α(T ), heat capacities, C V (T ) and C P (T ), entropy, S(T ) and bulk modulus, K(T ) of corundum are calculated in its entire range of thermal stability (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of VASP and OLCAO method in studying properties of different types of complex materials systems including metal [2,33,34], ceramics [35][36][37][38], and polymeric biomolecules [39,40] and liquid and amorphous solids [41,42] have been well demonstrated.…”
Section: Methods Used For Relaxation and Properties Calculationsmentioning
confidence: 99%